PENGARUH GAME INTERAKTIF WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR - Fitriani; Muzaini, Muhammad; Jaelani, Abd. Kadir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the use of interactive game learning media Wordwall on the mathematics learning outcomes of fifth-grade students of UPT SDN No. 78 Balang, Takalar Regency. The type of research used is quantitative research with a pre-experimental method using the One Group Pretest-Posttest Design. The population in this study were all fifth-grade students of UPT SDN No. 78 Balang, totaling 37 students, and the entire population was used as a research sample. Data collection techniques were carried out through learning outcome tests (pre-test and post-test) and observation. Data analysis used was descriptive statistical analysis and inferential statistical analysis with paired sample t-test. The results showed that the average pre-test score of students was 60.68 while the average post-test increased to 75.54 after the application of animated video learning media. This increase indicates a change in student learning outcomes after being given treatment in the learning process. The t-test results produced tcount = -19.496 with degrees of freedom (df) = 36 and a significance value (Sig. 2-tailed) = 0.001 < 0.118. This indicates that there is a significant difference between the pre-test and post-test results. Thus, it can be concluded that the use of interactive game learning media Wordwall has a positive and significant effect on improving the Mathematics learning outcomes of fifth-grade students of UPT SDN No. 78 Balang, South Galesong District, Takalar Regency.